5(x+4)/4=3x-3

Simple and best practice solution for 5(x+4)/4=3x-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x+4)/4=3x-3 equation:


x in (-oo:+oo)

(5*(x+4))/4 = 3*x-3 // - 3*x-3

(5*(x+4))/4-(3*x)+3 = 0

(5*(x+4))/4-3*x+3 = 0

(5*(x+4))/4+(-3*4*x)/4+(3*4)/4 = 0

5*(x+4)-3*4*x+3*4 = 0

12-7*x+20 = 0

32-7*x = 0

(32-7*x)/4 = 0

(32-7*x)/4 = 0 // * 4

32-7*x = 0

32-7*x = 0 // - 32

-7*x = -32 // : -7

x = -32/(-7)

x = 32/7

x = 32/7

See similar equations:

| P(20.0L)=(0.9089moles)(0.08205)(294K) | | 13200-250m= | | 3(x-4)-(5x-2)=3-2(4-3x)-3 | | 2=z/8 | | 12/y=15/20 | | 0.80x+0.80(10)=0.40(36) | | 9x+14=3x-4 | | 54x^2+84x=0 | | 450m= | | x=-750x^2+15000x | | 25y^2-51y+26= | | -2/3l-3=-5 | | -2/3l+3=-5 | | 8x^2+5=205 | | y=2(3a+7b) | | 2v^3+18v^2+40v=0 | | 4m^-5n^3/6m^4n^-4 | | 2c+10-c=7 | | ln(x-3)-ln(x+3)=ln(x-5) | | y=7x+9k | | 4x+5*16=15 | | y=(8+4k)x | | 0.5a-1.4=2.1 | | (12x^2-5x+4)/(3x+1) | | ln(x+1)+ln(x+3)=ln(3) | | m/2+9=5 | | -7ab(6a-4b-7)= | | 2h+19=6(-2)+u | | 9+2p=15 | | 3w^7-18w^6-165w^5= | | 5/7+9/7x=2/x^2 | | (7x-3)/3=2x |

Equations solver categories